Pengaruh Word of Mouth dan Brand Image terhadap Keputusan Memilih Layanan Rumah Sakit Pendidikan Universitas Hasanuddin - Indriani, Dian; Akbar, Muhammad; Arianto, Arianto (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
Hospitals are now public health service facilities that are not only socially oriented but also have business aspects. Increasingly tight competition between health service facilities requires hospitals to pay attention to the factors that underlie, direct and encourage patients' decisions in choosing a hospital, including word of mouth (WOM) communication and brand image. This study aims to determine the influence of WOM and brand image on the decision to choose outpatient services at Rumah Sakit Pendidikan Universitas Hasanuddin. This research was conducted using descriptive quantitative methods. Data collection was carried out by distributing questionnaires to 201 respondents. The sampling technique used was accidental sampling, namely distributing questionnaires to respondents who happened to be present or available in a place according to the research context. Processing research data using the SPSS version 25.0 application. Instrument testing was carried out using validity and reliability tests. Data testing was carried out using the classic assumption test. The analysis used is multiple regression analysis. Hypothesis testing was carried out using the t test and F test. The results of the study stated that there was an influence of word of mouth and brand image on the decision to choose hospital outpatient services both partially and simultaneously, but the influence of the WOM and brand image variables together (simultaneously). ) is only 33.8%, or can be said to have a weak influence.